Pengaruh Pendidikan Kewirausahaan, Pola Pikir Kewirausahaan Dan Lingkungan Keluarga Terhadap Minat Berwirausaha ( Studi Pada Mahasiswa Fakultas Ekonomi DanBisnis Universitas Islam Malang) - Farhan Abror; Pardiman Pardiman; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study It's to understand the impact of entrepreneurial education, entrepreneurial mindset and family environment on entrepreneurial interests to the Faculty of Economics and Business of The University of Islam Malang. Sample used in this study are 83 students. Data analysis method which is used in the research as a quantitative data analysis using multiple linear regression analysis. Data testing used is testing simultaneous hypothesis (F) and testing a partial hypothesis (t). Results studies show that these simultaneously influential independent variables is significant to a dependent variable. Based on partial testing results, entrepreneurial education variables, entrepreneurial mindset and environment the family is significant in the interest of faculty student entrepreneurs the economics and business of the islamic university are unfortunate. Keywords: Entrepreneurial Education, Entrepreneurial Mindset, Family Environment and Entrepreneurial Interests